Advancing LHC probes of dark matter from the inert two-Higgs-doublet model with the monojet signal - Belyaev, A. (2019)
The inert two- Higgs-doublet Model (i2HDM) is a well-motivated minimal consistent dark matter (DM) model, but it is rather challenging to test at the LHC in the parameter space allowed by relic density and DM direct detection constraints. This is especially true when considering the latest XENON 1T data on direct DM searches, which we use here to present the best current combined limit on the i2HDM parameter space. In this analysis, we present prospects to advance the exploitation of DM monojet signatures from the i2HDM at the LHC, by emphasising that a shape analysis of the missing transverse momentum distribution allows one to sizably improve the LHC discovery potential. For a key element of our analysis, we explore the validity of using an effective vertex, ggH, for the coupling of the Higgs boson to gluons using a full one-loop computation. We have found sizeable differences between the two approaches, especially in the high missing transverse momentum region, and incorporated the respective K-factors to obtain the correct kinematical distributions. As a result, we delineate a realistic search strategy and present the improved current and projected LHC sensitivity to the i2HDM parameter space.